Effects of gully topography on space-time patterns of soil moisture in a semiarid grassland - Melliger, Joshua J., author; Niemann, Jeffrey D., advisor; Butters, Greg, committee member; Bledsoe, Brian, committee member (Colorado State University. Libraries, 2009)
Gullies are pervasive topographic features in semiarid grasslands in North America. At the Army’s Piñon Canyon Maneuver Site (PCMS) in southeastern Colorado, gullies are important because they restrict the mobility of troops and vehicles in training exercises, and they represent areas that are potentially vulnerable to further erosion. Substantial research has examined the temporal evolution of gullies as well as the factors that initiate gullies and control their morphology. In particular, prolonged periods of low soil moisture (droughts), frequent flash floods, and human activity are thought to reduce vegetative cover and promote gully development. Much less is understood about the feedback of gully topography on space-time patterns of soil moisture. The presence of gullies may produce feedbacks to soil moisture that either enhance or diminish gully development. In this study, field observations from PCMS are used to study the effects of gullies on space-time patterns of soil moisture and to describe the interactions of soil moisture, soil texture, and vegetation around gullies. Three study sites at PCMS have been extensively instrumented. These sites are located in the same broad valley, but one site (~1500 m2) is ungullied while the other two sites (also ~1500 m2) each contain a gully. The gully sites are adjacent to each other and their two gullies are approximately parallel. Hourly soil moisture observations have been collected for 8 months at two sites and 4 months at one site using time domain reflectometry (TDR) probes installed along four transects within each site. Each transect contains 6-8 probes that are positioned at the mid-points between topographic breakpoints. Meteorological data are also collected at the ungullied site and between the two gullied sites. Overall, the occurrence of gullies was observed to not affect the spatial average soil moisture within the study sites, but the gullies do promote spatial variability in soil moisture. Gully bottoms tend to be wetter. Although the evidence here is not conclusive, this tendency may be due to gradual lateral inflows, thicker vegetation (which protects the soil against surface crusting and promotes infiltration), and the lower local elevations (which protect against higher wind speeds and evapotranspiration). The gully sidewalls tend to be drier because of rapid drainage during and after precipitation events and in some cases increased solar insolation.
Covers not scanned.
Keywords: Arroyos -- Colorado; Soil moisture -- Colorado; Erosion -- Colorado; Pinon Canyon Maneuver Site (Colo.)